Optimizing Criminal Sanctions Against Narcotics Crimes in Indonesia - Albri Labaka; Muh Endriyo Susila (Faculty of Law, Universitas Pekalongan, 2025)
This study discusses the application of criminal sanctions for narcotics crimes in Indonesia. It also aims to find solutions to legal problems by using juridical-normative research because it prioritizes the conception of LawLaw as a law in doctrine, which is entirely covered in a conceptual approach to research. Research results: First, the justification for applying sanctions against narcotics offenders is based on the theory of determinism and the values of Pancasila justice, according to mono-dualistic teachings in criminal law. Theoretically, the application of action sanctions is in line with several legal theories, including the Combined/Modern Criminal Theory (Verenings Theorien), the Restorative Justice Theory, and the Double Track System Theory. Second, the revision of the Narcotics Law must establish limits and requirements for the application of sanctions for actions related to the type of crime and the perpetrator of the crime. This is important to do when the law is changed in the future. Third, sanctions can be implemented in two ways: normative through the Brainwashin program, decriminalization programs, and health programs for women drug users, and social forms through the separation of corrections and the establishment of particular institutions for the implementation of action sanctions, which are under the jurisdiction of the Prosecutor's Office Agung and in the future there needs to be a special narcotics court.